2014
DOI: 10.2478/bvip-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Gross and histological evaluation of early lesions of navicular bone and deep digital flexor tendon in horses

Abstract: The study aimed at evaluation of pathological lesions on flexor surface of navicular bone and deep digital flexor tendon in horses graded in standard X-ray examination as 2 (fair). The evaluation was performed on fifteen horses (6-9 years of age). Analysis procedure involved examining navicular bones on X-ray pictures, post-slaughter preparation of navicular bones from the hoof capsule, macroscopic evaluation of fibrocartilage on flexor surface, and analysis of histologic preparations. In horses with navicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It seems, however, that the thinning of cartilage is the first symptom of lesions due to overload. Since analyses of this type were conducted in mammals, one may expect an analogy [32]. The other bird was regarded as a control.…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…It seems, however, that the thinning of cartilage is the first symptom of lesions due to overload. Since analyses of this type were conducted in mammals, one may expect an analogy [32]. The other bird was regarded as a control.…”
Section: Osteochondritis Dissecansmentioning
confidence: 99%
“…Because our study design suggested gross pathology as gold standard for diagnosing navicular disease in horses, histological changes were not taken into consideration (Blunden et al 2006a, b;Komosa et al 2014). This would particularly be a problem in early stages of the disease.…”
Section: Limitationsmentioning
confidence: 99%
“…This would particularly be a problem in early stages of the disease. Because no anamnestic information about the horses was available, especially regarding the presence of lameness, our ndings rated in gross pathology were based on ndings from other authors (Blunden et al 2006a, b;Komosa et al 2014) and are not necessarily associated with clinical lameness. Due to the preparation and gross pathological examinations of the surfaces exclusively, pathological changes in the DSIL, CSL, core defects in the DDFT, subchondral changes in the navicular bone and others were excluded from the examination.…”
Section: Limitationsmentioning
confidence: 99%
“…The accumulation of small injuries during gallop and jumping can be the key cause of pathological changes of the distal sesamoid bone. The type of ground most often used in training of the horse is also important (Komosa et al 2014).…”
Section: Breed and Morphotypementioning
confidence: 99%